Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12933-021-01244-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of soluble suppression of tumorigenesis-2 (sST2) for cardiovascular events in coronary artery disease patients with and without diabetes mellitus

Abstract: Background Soluble suppression of tumorigenesis-2 (sST2) is implicated in myocardial overload and has long been recognized as an inflammatory marker related to heart failure and acute coronary syndrome, but data on the prognostic value of sST2 in patients with coronary artery disease (CAD) remain limited. This study sought to investigate the prognostic value of sST2 in patients with established CAD and its predictive value in CAD patients with and without type 2 diabetes mellitus (T2DM). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…A short-term (180 days) follow-up study on patients with T2DM and HD showed that sST2 levels > 54 ng/mL were associated with a higher risk of death and rehospitalization for cardiovascular causes [ 43 ]. Another study showed that plasma sST2 levels ≥ 19 ng/mL significantly predicted the development of MACEs and other CV endpoints in patients with CAD after adjusting for age, sex, and presence of T2DM [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A short-term (180 days) follow-up study on patients with T2DM and HD showed that sST2 levels > 54 ng/mL were associated with a higher risk of death and rehospitalization for cardiovascular causes [ 43 ]. Another study showed that plasma sST2 levels ≥ 19 ng/mL significantly predicted the development of MACEs and other CV endpoints in patients with CAD after adjusting for age, sex, and presence of T2DM [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…By acting as a circulating decoy for interleukin-33 (IL-33), it prevents the cardioprotective effects of the ST2/IL-33 signaling, thus promoting maladaptive myocardial hypertrophy and cardiomyocyte apoptosis [ 18 ]. While a number of observational studies have investigated sST2 levels in T2DM [ 19 , 20 ], data on its prognostic role is limited to short follow-up periods, and its incremental value over the established cardiac biomarkers—BNP and cTn–has not been extensively assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [ 20 ] observed that patients with stable coronary artery diseases (CAD) and higher plasma levels in sST2 showed a 13.7-fold increase in major cardiovascular events (MACE)—namely, cardiac death, non-fatal myocardial infarction, coronary revascularization (90 days after ICA), and ischemic stroke. The risk for death in CAD patients with increased plasma concentration of sST2 was twofold higher as compared with those in the lowest percentiles [ 21 , 22 ]. Indeed, a meta-analysis from Liu et al [ 12 ] indicated that elevated baseline sST2 levels promote a 74% increase in the long-term risk of MACE in patients with the acute coronary syndrome (ACS), thus considering a possible implication of sST2 in vulnerable plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Serum sST2 is unaffected by potential confounding variables, including age, sex, body mass index, and comorbidities such as renal disease and diabetes ( 41 ), making it a promising biomarker. Relevant clinical investigations have confirmed that serum sST2 can be utilized as an additional parameter for the diagnosis and prognosis of cardiovascular illnesses such as coronary heart disease ( 42 , 43 ), aortic dissection ( 44 , 45 ), and HF ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%